I want to return to the muyuna, the whirlpool of my origins (2014)
In his paintings of fishes and fishermen, Pablo Taricuarima portrays the daily triumphs and resignations of his mother, father, brothers and uncles, a family of the Cocama people whose life comes and flows with the colors of Amazonian rivers. In his spatial interventions, he transports fishing technologies to the city and covers with nets, nests, shells and traps the squares and other few empty spaces left between the building and the cement.